2019
DOI: 10.1530/eje-19-0377
|View full text |Cite
|
Sign up to set email alerts
|

A somatic mutation in CLCN2 identified in a sporadic aldosterone-producing adenoma

Abstract: Objective To screen for CLCN2 mutations in apparently sporadic cases of aldosterone-producing adenomas (APAs). Description Recently, CLCN2, encoding for the voltage-gated chloride channel protein 2 (ClC-2), was identified to be mutated in familial hyperaldosteronism II (FH II). So far, somatic mutations in CLCN2 have not been reported in sporadic cases of APAs. We screened 80 apparently sporadic APAs for mutations in CLCN2. One somatic mutation was identified at p.Gly24Asp in CLCN2. The male patient had a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 14 publications
1
38
0
Order By: Relevance
“…Scholl et al studied the original kindred first described by Stowasser in 2018 and identified a gain-of-function early-onset germline variant in CLCN2 (p.R172Q) [ 28 ], in addition to 4 new rare germline CLCN2 variants (p.M22K, p.Y26N, p.K362del, and p.S865R) [ 28 ]. Concurrently, Fernandes-Rosa and colleagues identified a de novo germline CLCN2 mutation in a 9-year-old patient (p.G24D) [ 27 ] that was similar to the somatic APA mutation recently described by Dutta et al [ 31 ] as well as one of the somatic mutations reported in our study. Both groups performed functional studies wherein electrophysiological experiments in H295R-S2 and HEK293 cells transfected with wild-type and mutant CLCN2 demonstrated that the mutations caused increased activation of the Cl – channels leading to depolarization of the cell membrane and subsequent opening of the voltage-dependent Ca 2+ channels, confirming a gain-of-function mechanism.…”
Section: Discussionsupporting
confidence: 86%
“…Scholl et al studied the original kindred first described by Stowasser in 2018 and identified a gain-of-function early-onset germline variant in CLCN2 (p.R172Q) [ 28 ], in addition to 4 new rare germline CLCN2 variants (p.M22K, p.Y26N, p.K362del, and p.S865R) [ 28 ]. Concurrently, Fernandes-Rosa and colleagues identified a de novo germline CLCN2 mutation in a 9-year-old patient (p.G24D) [ 27 ] that was similar to the somatic APA mutation recently described by Dutta et al [ 31 ] as well as one of the somatic mutations reported in our study. Both groups performed functional studies wherein electrophysiological experiments in H295R-S2 and HEK293 cells transfected with wild-type and mutant CLCN2 demonstrated that the mutations caused increased activation of the Cl – channels leading to depolarization of the cell membrane and subsequent opening of the voltage-dependent Ca 2+ channels, confirming a gain-of-function mechanism.…”
Section: Discussionsupporting
confidence: 86%
“…It was the first time that implication of a chloride channel was shown in the regulation of aldosterone production. A recent study also found 1 somatic mutation in CLCN2 , after screening 80 apparently sporadic APAs, in a male patient with PA, which was cured after surgery of its small adenoma [ 103 ].…”
Section: Benign Adrenal Tumors Associated With Primary Hyperaldostmentioning
confidence: 99%
“…β-Catenin (CTNNB1) mutations were also identified in a small percentage of APA and a recent study suggests that these mutations may be associated with the process of tumorigenesis rather than direct activation of aldosterone production [29]. Recent studies have demonstrated a small percentage of APA harboring somatic mutations in the voltage-gated chloride channel type 2 (CLCN2) [30] and the calcium channel-gated channel subunit alpha 1H (CAC-NA1H), which were originally shown to cause germline PA [31][32][33][34]. Recent application of aldosterone synthase (CYP11B2)-guided cap-ture of APA followed by higher depth gene-targeted NGS suggests that greater than 90 % of APA have aldosterone-driver mutations [24,26].…”
Section: Overview Of Primary Aldosteronism (Pa)mentioning
confidence: 99%